Is international monetary policy coordination feasible for the ASEAN-5 + 3 countries? - Eric Alexander Sugandi (Asian Development Bank Institute (ADBI), 2020)
This study examines the feasibility of international monetary policy coordination among the ASEAN-5 + 3 countries using the two-production-factor dynamic stochastic general equilibrium (DGSE) model. It explores three types of interaction regimes among these countries: "no coordination," "bilateral coordination," and "multilateral coordination." This study defines the benefit of international monetary policy coordination as the improvement of welfare (in terms of macroeconomic stability) for the participating countries. The cost of policy coordination is the loss of flexibility for the central banks of the participating countries to conduct monetary policy in the presence of shocks. A coordination scheme is feasible when the benefit of such coordination exceeds the cost for each of the participating countries. This study finds 18 feasible bilateral coordination schemes (out of 28 schemes) and 4 feasible multilateral coordination schemes (out of 6 schemes) for the ASEAN-5 + 3 countries, of which the ASEAN-5 + 3 multilateral monetary policy coordination is the best feasible scheme. The outcomes of multilateral policy coordination tend to be better than those of bilateral policy coordination. The relative size of the participating countries is a dominant factor that determines the feasibility of policy coordination. Nonetheless, it is possible to have feasible coordination when there are big differences in size among the participating countries, provided that there are other factor(s) with a significant influence on welfare in these countries, such as strong trade and direct investment linkages.
Keywords: F41; F42; 330; international monetary policy coordination; open economy macroeconomics